1937
DOI: 10.1017/s0021859600051649
|View full text |Cite
|
Sign up to set email alerts
|

A study of the fasting metabolism of various breeds of hog: III. Metabolism and surface area measurements.

Abstract: From metabolism experiments carried out on the pigs enumerated in the first paper of this series the following conclusions are drawn:(a) The metabolism in a state of inanition appears to be more a function of a power of the weight than of the true surface area as determined by the photographic method.(b) Hogs born in the summer and autumn of one year appear to show two maxima of metabolism; one almost immediately, as has been observed previously, and another during the following summer, provisionally ascribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1955
1955
1974
1974

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Nevertheless, it is apparent from the literature that seasonal differences in performance do sometimes exist, but whether or not these are due to fluctuations in environmental temperature or to some other factor such as length of day is not clear. Deighton (1937), from animalcalorimeter studies, concluded that 'hogs born in the summer and autumn of one year appear to show two maxima of (resting) metabolism, one almost immediately. .…”
mentioning
confidence: 99%
“…Nevertheless, it is apparent from the literature that seasonal differences in performance do sometimes exist, but whether or not these are due to fluctuations in environmental temperature or to some other factor such as length of day is not clear. Deighton (1937), from animalcalorimeter studies, concluded that 'hogs born in the summer and autumn of one year appear to show two maxima of (resting) metabolism, one almost immediately. .…”
mentioning
confidence: 99%